The last glacial termination on the eastern flank of the central Patagonian Andes (47ºS) - Henríquez, William I.; Villa-Martinez, Rodrigo; Vilanova, Isabel; De Pol-Holz, Ricardo; Moreno, Patricio
Few studies have examined in detail the sequence of events during the last glacial termination (T1) in the core sector of the Patagonian Ice Sheet (PIS), the largest ice mass in the Southern Hemisphere outside of Antarctica. Here we report results from Lago Edita (47°8′ S, 72°25′ W, 570 m a.s.l.), a small closed-basin lake located in a valley overridden by eastward-flowing Andean glaciers during the Last Glacial Maximum (LGM). The Lago Edita record shows glaciolacustrine sedimentation until 19 400 yr BP, followed by organic sedimentation in a closed-basin lake and a mosaic of cold-resistant hygrophilous conifers and rainforest trees, along with alpine herbs between 19 400 and 11 000 yr BP. Our data suggest that the PIS retreated at least ∼ 90 km from its LGM limit between ∼ 21 000 and 19 400 yr BP and that scattered, low-density populations of cold-resistant hygrophilous conifers, rainforest trees, high-Andean and steppe herbs thrived east of the Andes during the LGM and T1, implying high precipitation levels and southern westerly wind (SWW) influence at 47° S. The conifer Podocarpus nubigena increased between 14 500 and 13 000 yr BP, suggesting even stronger SWW influence during the Antarctic Cold Reversal, after which it declined and persisted until 11 000 yr BP. Large increases in arboreal pollen at ∼ 13 000 and ∼ 11 000 yr BP led to the establishment of forests near Lago Edita between 10 000 and 9000 yr BP, suggesting a rise in the regional tree line along the eastern Andean slopes driven by warming pulses at ∼ 13 000 and ∼ 11 000 yr BP and a subsequent decline in SWW influence at ∼ 11 000 yr BP. We propose that the PIS imposed a regional cooling signal along its eastern, downwind margin through T1 that lasted until the separation of the northern and southern Patagonian ice fields along the Andes during the Younger Dryas period. We posit that the withdrawal of glacial and associated glaciolacustrine environments through T1 provided a route for the dispersal of hygrophilous trees and herbs from the eastern ...